Meta-Analysis Study Of The Effect Of Cigarette Smoke Exposure On The Incidence Of Pulmonary Tuberculosis In Children - Andi Muhammad Risal; Andi Husni Esa Darussalam; Hasmawaty Basir (Sean Institute, 2024)
The child population has a higher risk of being exposed to tuberculosis compared to the adult population. Children who are exposed to cigarette smoke from adults in the home environment, both children and adults have a high risk of being infected with tuberculosis. This study aims to determine the effect of exposure to cigarette smoke on the incidence of pulmonary tuberculosis in children. This research uses the Meta-analysis method using RevMan 5.4.1 software. Data estimation using the Random Effect Model from 7 pieces of literature with the number of samples and controls being 518 and 1,294 individuals. It was found that the RR of exposure to cigarette smoke on pulmonary tuberculosis was 1.67 (CI95% 1.18 – 2.36). So children who are exposed to cigarette smoke have a 1.67 times higher risk of developing pulmonary tuberculosis compared to those who are not. Exposure to cigarette smoke increases the risk of pulmonary tuberculosis in children, this can be observed in the greater number of cases of pulmonary tuberculosis in children in groups exposed to cigarette smoke compared to those who are not. Almost half of pulmonary tuberculosis in children can be prevented if exposure to cigarette smoke can be avoided in children.